Increased connectivity of insula sub-regions correlates with emotional dysregulation in patients with first-episode schizophrenia. (October 2022) - Zhang, Meng; Yang, Fude; Fan, Hongzhen; Fan, Fengmei; Wang, Zhiren; Xiang, Hong; Huang, Wenqian; Tan, Yunlong; Tan, Shuping; Hong, L. Elliot
Highlights: Investigation of insula subregion-based functional networks in patients with first episode schizophrenia (FES). FES patients exhibit abnormal functional connectivity of insula subregions. Altered anterior insula-anterior middle cingulate cortex connectivity correlated with emotional regulation deficiency in FES patients. ABSTRACT: Dysfunctional insula is crucial in the development of social cognition deficits, especially emotional dysregulation in patients with schizophrenia. However, function networks of insula sub-regions in schizophrenia are rarely investigated. In this study, functional connectivity between insula sub-regions and whole-brain voxels and its relationship with social cognition ability were investigated in patients with first-episode schizophrenia (FES). This study included 47 patients with FES and 47 healthy controls (HCs). Resting-state functional connectivity (rsFC) was assessed using a seed-based approach, and social cognition was measured by the "managing emotions" branch of the Mayer–Salovey–Caruso Emotional Intelligence Test. Differences in rsFC of insula sub-regions between the two groups were examined. Patients with FES showed increased rsFC between the left anterior insula (AI) and the right inferior frontal gyrus or the right anterior middle cingulate cortex (aMCC) and between the right middle insula and the right aMCC. Moreover, the increased AI-aMCC connectivity correlated negatively with the "managing emotion" scores in patients. This study highlights the altered functional connectivity of insula sub-regions and its correlation with emotional dysregulation in patients with FES. Our findings provide some insights into underlying neuropathological mechanisms associated with emotional regulation deficiency in patients with schizophrenia.